2004
DOI: 10.1074/jbc.m401912200
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-induced Smooth Muscle Cell Growth Is Regulated by Tuberin and Associated with Altered Activation of Platelet-derived Growth Factor Receptor-β and ERK-1/2

Abstract: The mechanisms that regulate the diverse responses to estrogen (E 2 ) are unknown. Loss of function of the tuberous sclerosis 2 gene (TSC2), a tumor suppressor gene, has been associated with a growth-promoting effect of E 2 . We hypothesized that tuberin, the protein product of TSC2, binds to estrogen receptors (ER) and regulates the growth effect of E 2 . An in vivo association between full-length tuberin and ER␣ was observed in HEK 293 cells and ELT-3 smooth muscle cells. In contrast, poor association was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 56 publications
6
51
0
2
Order By: Relevance
“…This pathway is inhibited in cells lacking TSC2 via Rheb's inhibition of B-Raf and C-Raf/Raf-1 kinase (13,14). E 2 has been shown to activate p42/44 MAPK in ELT3 cells and in LAM patient-derived cells (11,20,21). To confirm that E 2 activates MAPK in ELT3 cells, we treated the cells with 10 nM E 2 and examined the phosphorylation status of p42/44 MAPK by immunoblotting.…”
Section: Estrogen Activates P42/44 Mapk In Elt3 Cells In Vitro and Inmentioning
confidence: 99%
“…This pathway is inhibited in cells lacking TSC2 via Rheb's inhibition of B-Raf and C-Raf/Raf-1 kinase (13,14). E 2 has been shown to activate p42/44 MAPK in ELT3 cells and in LAM patient-derived cells (11,20,21). To confirm that E 2 activates MAPK in ELT3 cells, we treated the cells with 10 nM E 2 and examined the phosphorylation status of p42/44 MAPK by immunoblotting.…”
Section: Estrogen Activates P42/44 Mapk In Elt3 Cells In Vitro and Inmentioning
confidence: 99%
“…Moreover, the normal feedback mechanisms that limit cell proliferation can be blocked by rapamycin. Finally, TSC2 and Rheb participate in signaling mechanisms other than the mTOR pathway that contribute to the cytoskeletal, 132 hormonal, 137 and proliferative 142 characteristics of neoplastic cells. Further characterization of the mTOR complexes and their signal integration functions will lead to therapeutic approaches for LAM and neoplasia that simultaneously target multiple receptors and signaling intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…[136][137][138][139] Separate studies suggested that prolactin stimulates mTOR, and modifies STAT1 activity in mTOR-dependent fashion. 140,141 Further studies are required to better understand how mTORCs interact with androgen or estrogen signaling pathways.…”
Section: Other Emerging Mtor Targets In Lammentioning
confidence: 99%
“…33 Estrogen treatment of Tsc2-null ELT3 cells or TSC2-null LAMassociated angiomyolipoma cells is associated with strong and rapid (5 min) ERK-1=2 activation, suggesting that estrogen may have cytoplasmic ''nongenomic'' effects on LAM cells as well as genomic effects. [34][35][36] An interaction between tuberin and the estrogen receptor has been observed, [35][36][37] although its role in LAM pathogenesis remains unknown.…”
Section: Estrogen Promotes the Survival And Metastasis Of Tsc2-null Cmentioning
confidence: 99%